Telemedicine dalam Konstruksi Hukum di Indonesia - Mahindra Awwaludin Romdlon; Lutfi Kalbu Adi; Aris Aji Kurniawan (Universitas Muhammadiyah Purwokerto, 2021)
The Covid-19 pandemic that occurs in the world is one of the challenges that must be addressed by following technological developments. Telemedicine is currently an alternative in doctor-patient communication by taking advantage of technological developments in the Industrial Revolution 4.0. This study uses a normative legal method with an approach to telemedicine theories, regulations, and cases. The formulation of the problem raised in this study is about the benefits of telemedicine in general and the confidentiality of patient medical data and information. Telemedicine can reach all levels of society, especially with the geographical conditions in Indonesia and the uneven distribution of health workers. Telemedicine makes it easy for the public to conduct consultation and communication with health service facilities. The aspect of protecting patient medical data and information is one of the things that need to be considered in this telemedicine service because it is something that is regulated in layers through Law No. 29 of 2004 concerning Medical Practice, Law no. 36 of 2009 concerning Health, Regulation of the Indonesian Medical Council (Perkonsil) No. 74 of 2020.Keywords: Telemedicine, Benefits, Confidentiality